Clinical features of acute acquired comitant esotropia in the Chinese populations. Issue 46 (November 2017) - Fu, Tao; Wang, Jing; Levin, Moran; Xi, Ping; Li, Dongguo; Li, Junfa
Abstract : Abstract: Acute acquired comitant esotropia (AACE) is an unusual presentation of esotropia that occurs after infancy. This study was aimed to study the clinical features and the differences between children and adult patients with AACE in the Chinese populations. This was a retrospective analysis of patients diagnosed with AACE over 4 years; 69 patients (25 females and 44 males) were identified. The patients were divided into 3 groups: < 10 year-old (n = 6, 8.7%), 10–18 year-old (n = 23, 33.3%), and ≥18 year-old (n = 40, 58.0%). Patients underwent medical history, brain and orbital computed tomography, and ophthalmological and orthoptic examinations. The refractions of AACE patients varied among age groups: patients < 10 year-old had mild hypermetropia, while older children and adults showed moderate-to-high myopia ( P < .001). The mean angles of esotropia were significantly larger in young children compared with older children and adults ( P = .005). There was no significant difference in binocularity detected by either synoptophore or TNO stereoscopic testing among different disease durations. Stereopsis detected by synoptophore and TNO testing showed no significant difference at duration within half a year, but the stereopsis measured by TNO was significantly worse than that detected by synoptophore with extending disease duration ( P < .05). AACE seems to occur mostly in older children and adults in the Chinese population. Younger children with AACE seem to demonstrate a common trait of mild hypermetropic refractive errors, while myopia can be seen in older children and adult patients. The duration from onset to treatment of esotropia does not affect the preoperative binocularity.